2021
DOI: 10.3390/ijerph19010150
|View full text |Cite
|
Sign up to set email alerts
|

Physical Intimate Partner Violence, Childhood Physical Abuse and Mental Health of U.S. Caribbean Women: The Interrelationship of Social, Contextual, and Migratory Influences

Abstract: The literature has shown an increased risk for mental health conditions among victims of domestic violence. Few studies have examined the relationship between mental health disorders and domestic violence among Caribbean women, and how the association might be influenced by migratory and contextual factors. This study addresses the mental well-being of U.S. Caribbean Black women victims of domestic violence, and the relationships between acculturation, discrimination, and demographic influences. An analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
(54 reference statements)
1
2
0
1
Order By: Relevance
“…Also, a substantial relationship exists between verbal violence, AD and GAD, this is in line with the findings of Hegarty et al (2013), Lacey et al (2022), Nathanson et al (2012) and Siddiqui et al (2021) studies. Moreover, the study a reveals a substantial relationship between social violence, ODD and MD, suggesting that children with higher levels of ODD may be associated with exposure to higher levels of domestic violence.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Also, a substantial relationship exists between verbal violence, AD and GAD, this is in line with the findings of Hegarty et al (2013), Lacey et al (2022), Nathanson et al (2012) and Siddiqui et al (2021) studies. Moreover, the study a reveals a substantial relationship between social violence, ODD and MD, suggesting that children with higher levels of ODD may be associated with exposure to higher levels of domestic violence.…”
Section: Discussionsupporting
confidence: 88%
“…This study contributes to existing research by providing evidence of the potential mental health effects associated with children's exposure of domestic violence (Ahmadzad-Asl et al, 2016;Ferrari et al, 2016;Lacey et al, 2022). The findings support previous studies that have consistently shown a strong link between domestic violence and mental health disorders in children, including attention deficit hyperactivity disorder, conduct disorder, oppositional defiant disorder, generalized anxiety disorder, separation anxiety disorder and mood disorder as forms of mental health disorders found in children (Al Majali and Alsrehan, 2019;Chen et al, 2020;Curtis et al, 2015;Gul and Gurkan, 2018;Kehkashan Arouk, 2017;Okado and Bierman, 2015;Sanderud et al, 2016;Trevillion et al, 2012).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Anak tidak melanggar prinsip sopan santun meskipun menggunakan bentuk permintaan langsung pada sasaran, begitu juga mitra tuturnya merasa tidak dilanggar hak dan harga dirinya. Hal ini sejalan dengan pandangan bahwa tingkat kedekatan hubungan atau keakraban antara penutur dan mitra tutur berbanding terbalik dengan tingkat kesantunan yang diperlukan dalam berkomunikasi Lacey et al (2022) ;Rusbiyantoro (2014).…”
Section: Permintaan Anak Usia Dini (Usia 6 Tahun) Langsung Ke Sasaranunclassified